The Effects of Audit Fees, Audit Rotation, and Audit Tenure on Audit Quality, wirh the Audit Committee as a Moderator - Viriyayudha Satria Widjaja; Temy Setiawan; Margareta Febe; Andriati Fitriningrum (Owner : Riset dan Jurnal Akuntansi, 2026)
This study examines the effects of audit fees, audit rotation, and audit tenure on audit quality, with the audit committee as a moderating variable and leverage and firm size as control variables. The research employs a quantitative approach using secondary data from 50 energy sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2022–2024, resulting in 150 observation samples selected through purposive sampling. Multiple linear regression analysis was used to test the hypotheses. The results indicate that audit fees, audit rotation, and audit tenure each have a positive and significant effect on audit quality, suggesting that proportional fee-setting, periodic auditor rotation, and a measured engagement period contribute to improved audit quality. Leverage also has a significant effect on audit quality, while firm size exhibits a significant negative effect, reflecting the complexity challenges that large companies pose for auditors. With respect to moderation, the audit committee strengthens the relationship between audit fees and audit quality, but weakens the relationships between audit rotation and audit tenure with audit quality, implying that overly intensive oversight may be counterproductive under certain conditions. These findings reaffirm the relevance of agency theory in explaining the importance of effective governance mechanisms in maintaining audit quality in the energy sector